Penerapan Metode Pembelajaran Kooperatif Tipe Talking Stick untuk Meningkatkan Aktivitas dan Prestasi Belajar Agama Hindu dan Budi Pekerti - Sulistyani, Putu Eka; Suastini, Ni Nyoman; Gara, I Wayan (Jurnal Widya Sastra Pendidikan Agama Hindu, 2023)
This research is a classroom action research entitled "Implementation of the Talking Stick Cooperative Learning Method to Increase Activities and Achievements in Hinduism and Moral Learning for Class X TKJ SMK TI Bali Global Singaraja Academic Year 2022/2023. Data were collected using the data collection method and analyzed quantitative descriptions then the results obtained based on observations, activities and learning achievements of class X TKJ SMK TI Bali Global Singaraja, can be categorized as still very low. Judging from the above phenomenon, this study aims to increase the activity and learning achievement of class X students of TKJ Bali Global Singaraja TI Vocational School by trying to apply the Talking Stick Type Cooperative method. The research subjects were class X TKJ SMK TI Bali Global Singaraja Academic Year 2022/2023. In this study, the Cooperative Method of the Talking Stick Type was used in the subjects of Hinduism and Ethics. In this study the researchers set targets in the class average (M) 80, Absorption Power (DS) 80%, Mastery Learning Classical 80% and activity 80%. Judging from the results of this study, that the application of the Talking Stick Type Cooperative method can increase learning activity and achievement in the subject of Hinduism and morals. These results are indicated by an increase in the results of learning activities in the first cycle of 29% and the second cycle to 83%. Student achievement also increased, namely in the first cycle the class average (M) was 70.5, the absorption power (DS) was 70.5%, the learning mastery was 30% and the second cycle became the class average (M) 87.5, the learning achievement absorption (DS) 87.5%, and classical learning completeness 100% from KKM 70. From the research results that have been achieved this can be implemented by recommending all Hindu Religion Teachers, especially Hindu Religion teachers to apply the Talking Stick Type Cooperative method as an effort to increase the quality and quality of student education in the field of Hindu religious education and morals, in the form of evidence of students' learning activities and achievements that are getting better.